Increased nuchal translucency: it’s not just aneuploidy - Bhatt, Reema Kumar; Dwivedi, Pranjali; Rana, Anubhuti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Nuchal translucency (NT) measurement between 11- and 14-weeks’ gestation is an established and consistently performing marker for chromosomal abnormalities, including trisomy 21. Even in the absence of aneuploidy in the event of normal conventional karyotyping or microarray analysis, increased NT is prognosticative of adverse pregnancy outcome, because it is associated with miscarriages, congenital heart defects, several fetal malformations, many genetic syndromes, skeletal dysplasia’s, intrauterine death; the majority of these structural anomalies are undetectable before birth. The parents should be reassured that in the absence of any abnormality detected the fetus will have a normal uneventful outcome and postnatal development when compared to the general population outcome.